2018
DOI: 10.1101/464123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abrogation of Stem Loop Binding Protein (Slbp) function leads to a failure of cells to transition from proliferation to differentiation, retinal coloboma and midline axon guidance deficits

Abstract: Through forward genetic screening for mutations affecting visual system development, we identified prominent coloboma and cell-autonomous retinal neuron differentiation, lamination and retinal axon projection defects in eisspalte (ele) mutant zebrafish. Additional axonal deficits were present, most notably at midline axon commissures. Genetic mapping and cloning of the ele mutation showed that the affected gene is slbp, which encodes a conserved RNA stem-loop binding protein involved in replication dependent h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Markers z7256 and z10008 flanked a ∼12.6 Mb interval containing 183 genes. Next generation sequencing, combined with a slightly modified version (Turner et al, 2019) of the Variant Discovery Mapping (VDM) CloudMap pipeline (Minevich et al, 2012) pipeline confirmed and refined this position. Instead of plotting individual allele frequencies, the kernel density of homozygous/heterozygous SNPs was plotted along each chromosome.…”
Section: Loss-of-function Allelementioning
confidence: 83%
“…Markers z7256 and z10008 flanked a ∼12.6 Mb interval containing 183 genes. Next generation sequencing, combined with a slightly modified version (Turner et al, 2019) of the Variant Discovery Mapping (VDM) CloudMap pipeline (Minevich et al, 2012) pipeline confirmed and refined this position. Instead of plotting individual allele frequencies, the kernel density of homozygous/heterozygous SNPs was plotted along each chromosome.…”
Section: Loss-of-function Allelementioning
confidence: 83%
“…Therefore we performed immunostaining of the axonal projections in three-day-190 old zebrafish larvae and looked at the expression patterns along the midline in the 191 ventral forebrain, where Slit3 is known to be expressed (32). No differences between 192 Slbp ty77e/ty77e were used as positive control for antibody staining, as these mutants have 208 fewer neurons and show axonal defects (33). n=10 samples per genotype group.…”
Section: Characterisation Of Slit3 Sa1569 Mutants 187mentioning
confidence: 99%
“…In humans, a subpopulation of colobomata is a result of mutations in developmentally important genes, however, the origins for many OF closure defects are unknown (for reviews, see (3,7,8,13,14)). Additional genes have been identified in animal models; substantial progress has been made in understanding critical processes, including growth and patterning of the ventral optic cup and optic nerve head (15- 19), cell-cell contact and signaling (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), crosstalk with migrating hyaloid precursors and extracellular matrix components (31)(32)(33)(34)(35)(36), cytoskeleton dynamics (37,38), epigenetics (39), degradation of ECM and cellular proteins (40)(41)(42), programmed cell death, survival and cell proliferation (43,44) (for reviews, see (7,8,13)). Elegant in vivo imaging studies in zebrafish and excellent anatomical analyses in chick have characterized important morphogenetic and cellular behavior (20,27,34,(45)(46)(47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%